Pre-stroke Physical Inactivity and Stroke Severity in Male and Female Patients - Salmantabar, Pegah; Abzhandadze, Tamar; Viktorisson, Adam; Reinholdsson, Malin; Sunnerhagen, Katharina S. (Frontiers in Neurology, 2022)
Introduction Females experience more severe ischemic strokes than do males. A higher pre-stroke physical activity level is associated with less severe stroke. The primary aim of this study was to explore the association between pre-stroke physical inactivity and stroke severity in male and female patients. Methods This was a retrospective, registry-based study. The data were retrieved from two stroke registries from 2014 to 2019. The primary explanatory variable was physical activity level before the stroke, assessed using the Saltin-Grimby Physical Activity Level Scale. The outcome was moderate to severe stroke at hospital admission, assessed using the National Institutes of Health Stroke Scale (NIHSS). A moderate to severe stroke was defined as a NIHSS score of ≥6. Binary logistic regression analysis was performed to explore if physical inactivity before the stroke could explain stroke severity in male and female patients. Results In total, we included 4,535 patients with ischemic stroke. Female patients (n = 2,145) had a mean age of 76 years, 35% had a moderate to severe stroke, and 64% were physically inactive pre-stroke. Male patients (n = 2,390) had a mean age of 72 years, 25% had a moderate to severe stroke, and 49% were physically inactive pre-stroke. Physical inactivity was associated with higher odds for moderate to severe stroke in both sexes (females' odds ratio [OR], 2.7, 95% confidence interval [CI]: 2.2–3.3, p < 0.001 and males' OR, 2.06, 95% CI: 1.7–2.5, p < 0.001). The association remained significant in the adjusted models. Conclusions Physically inactive females and males had higher odds of experiencing a moderate to severe stroke. However, the OR of female patients was somewhat higher than that of male patients.